2011
DOI: 10.1007/s11262-011-0594-8
|View full text |Cite
|
Sign up to set email alerts
|

Watermelon chlorotic stunt virus (WmCSV): a serious disease threatening watermelon production in Jordan

Abstract: The incidence of watermelon chlorotic stunt disease and the molecular characterization of the Jordanian isolate of Watermelon chlorotic stunt virus (WmCSV-[JO]) are described in this study. Symptomatic leaf samples obtained from watermelon (Citrullus lanatus Thunb.), melon (Cucumis melo L.), squash (Cucurbita pepo), cucumber (Cucumis sativus L.), and bottle gourd (Lagenaria siceraria) plants were tested for WmCSV-[JO] infection by PCR. The virus could be detected in 8 melon and 87 watermelon samples obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 37 publications
0
19
1
Order By: Relevance
“…Leaf samples collected from Jenin and Qalqilia were found to be mixed infected with WmCSV-[PAL] and SLCV-[PAL] (48%). Mixed infections with two or three whitefly transmitted viruses were also very common in cucurbits fields in Lebanon and Jordan [16,24]. Moreover, recent results have demonstrated that co-infection of melon plants with both WmCSV and SLCV results in a synergistic reaction characterized by severe symptoms and a major yield reduction [6,39].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Leaf samples collected from Jenin and Qalqilia were found to be mixed infected with WmCSV-[PAL] and SLCV-[PAL] (48%). Mixed infections with two or three whitefly transmitted viruses were also very common in cucurbits fields in Lebanon and Jordan [16,24]. Moreover, recent results have demonstrated that co-infection of melon plants with both WmCSV and SLCV results in a synergistic reaction characterized by severe symptoms and a major yield reduction [6,39].…”
Section: Resultsmentioning
confidence: 99%
“…DNA-A contains five ORFs, which encode for proteins involved in replication, regulation of gene expression, and encapsidation, while DNA-B contains two ORFs, encoding for proteins involved in viral movement and symptom development [7,8]. Begomoviruses have spread rapidly among cucurbit crops throughout the world, and such invasions were caused by Squash leaf curl virus (SLCV) [6,9,10,11], Cucurbit leaf curl virus (CuLCV) [12], Melon chlorotic leaf curl virus (MCLCuV) [13,14] and Watermelon chlorotic stunt virus (WmCSV) [6,15,16,17,18]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tomato yellow leaf curl virus (TYLCV) has a monopartite genome [29] while that of Watermelon chlorotic stunt virus (WmCSV) is bipartite with a DNA-A and a DNA-B genomic component [11]. Both cause serious crop diseases: WmCSV threatens the production of cucurbit crops like watermelon ( Citrullus lanatus ), melons ( Cucumis melo ), and pumpkin ( Cucurbita moschata ) in North Africa, Yemen, Israel, Jordan and Iran [12]. Disease symptoms include vein yellowing, chlorotic mottling and stunting and severe curling of leaves with drastic reduction of yield [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…Sequence analysis revealed that the diseases were caused by the native Watermelon chlorotic stunt virus and Squash leaf curl virus Abudy et al, 2010;Ali-Shtayeh et al, 2014;Idris et al, 2006). WmCSV was first identified in Yemen (Jones et al, 1988) and after that, in the following years, it was reported through the Middle East and also in North Africa as the following: Sudan (Kheyr-Pour et al, 2000), Jordan (Al-Musa et al, 2011), Oman (Khan et al, 2012) and Palestine (Ali-Shtayeh et al, 2014). The symptoms caused by WmCSV are chlorotic mottling, vein yellowing, stunting and severe decrease of yield, generally in watermelon (Citrullus species) crops.…”
Section: Introductionmentioning
confidence: 99%